Perbandingan Tekanan Intraokular (Tio) Sebelum Dan Sesudah Operasi Fakoemulsifikasi Pada Pasien Katarak Senilis Di Rumah Sakit Mata Makassar Tahun 2025 - Sitti Ma’rifa; Andi Senggeng Relle; Nursapriani (RS Mata Makassar, 2025)
One of the complications that may occur after phacoemulsification is an increase in intraocular pressure This complication can occur both during and after cataract surgery. Measuring IOP before and after surgery is crucial for detecting potential increases in IOP. To determine the comparison of IOP before and after phacoemulsification surgery in patients with senile cataracts. This study used a one-group pre-test and post-test design. This is a quantitative study with a pre-experimental approach. The sample in this study was selected using purposive sampling, involving 78 individuals who underwent phacoemulsification surgery. The results of the Paired Sample Test showed that the pre-operative IOP compared to the post-operative IOP M3 had a mean difference of -1.78 with p = 0.000 (p < 0.05). This indicates a decrease in IOP in the third week post-surgery compared to pre-surgery in phacoemulsification surgery for senile cataract patients, and this decrease was statistically significant. In this study, there was an increase and decrease in intraocular pressure (IOP) before and after phacoemulsification surgery in patients with senile cataractsat Makassar Eye Hospital in 2025.